Simplifying the diagnosis of optic tract lesions - Cohen-Sinai, Noa; Man-Peles, Inbal; Zahavi, Alon; Luckman, Judith; Goldenberg-Cohen, Nitza (Frontiers in Medicine, 2022)
Optic tract lesions (OTL) are often difficult to diagnose. We suggest an algorithm to simplify the often-challenging diagnosis of OTL. Clinical and imaging data were retrospectively collected from the electronic files of 6 patients diagnosed with OTL at a tertiary medical center in 2016–2020. The series included 4 children and 2 adults with an OTL caused by a glioma (n = 5) or motor vehicle accident (n = 1). Magnetic resonance imaging (MRI) revealed a suprasellar glioma involving the chiasm and tract alone (n = 1) and the ipsilateral optic nerve (n = 2) and only optic tract (3). Perimetry showed incongruent homonymous hemianopia in 3 patients. In two patients, perimetry could only be performed in one eye, and demonstrated hemianopia. In one patient perimetry was unreliable. Fundus examination revealed bow-tie atrophy in all patients. On optical coherence tomography (OCT) of the peripapillary retinal nerve fiber layer (RNFL) horizontal thinning was observed in the contralateral eye (n = 6). By presenting the information in a predefined order—visual field damage, OCT RNFL thickness, and MRI—the diagnosis could be easily reached even in children, and when other structures like the chiasm were involved. Fundus photographs easily detect bow tie atrophy in children. Systematic presentation of the data in a predefined order can ease the diagnostic process of OTLs.